Focusing on the Interactions between the GABAergic System and Neurosteroids in Neurodevelopmental Disorders - Fanelli, Francesca; Marino, Ramona; Keller, Flavio (Current Pharmaceutical Design, 2013)
Neurosteroids play essential roles in the control of central nervous system functions during physiological and pathological conditions. Increasing evidences show gender differences in the pathogenesis and clinical manifestations of several neurodevelopmental conditions, including Autism Spectrum Disorders (ASD), possibly due to the action of sex hormones during critical periods of brain development. Furthermore, it is known that neuroactive steroids contribute to neuroprotection, spinogenesis, synaptogenesis, as well as to modulation of neuronal excitability via their interaction with GABA receptors. Dysfunctions of GABAergic signaling early in development lead to a severe excitation-inhibition unbalance in neuronal circuits, which may contribute to the pathophysiology of autism. In this review, we summarize recent data concerning the functional role of neurosteroids and their relationship with the GABAergic system, focusing on GABA-mediated neurotrasmission alterations characterizing some neurodevelopmental disorders.
Keywords: neurodevelopmental disorders